The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1177/089686080402400416
|View full text |Cite
|
Sign up to set email alerts
|

PD Fluids Contain High Concentrations of Cytotoxic GDPs Directly after Sterilization

Abstract: Objective Glucose degradation products (GDPs) in peritoneal dialysis (PD) fluids are cytotoxic and affect the survival of the peritoneal membrane. One of the most reactive GDPs in PD fluids is 3,4-dideoxyglucosone-3-ene (3,4-DGE). 3,4-DGE has been reported as an intermediate between 3-deoxyglucosone (3-DG) and 5-hydroxymethyl furaldehyde (5-HMF) during degradation of glucose. In PD fluids, 3,4-DGE exists in a temperature-dependent equilibrium with a pool of unidentified substances. The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 23 publications
(28 reference statements)
7
64
0
1
Order By: Relevance
“…In addition, GO was not detected when sterilized in the conventional treatments. These results are in line with previously reported concentrations, by Erixon et al [2] and Okabe et al [34]. This observation indicates that the composition being used in this study as well as the analytical procedures is adequate.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, GO was not detected when sterilized in the conventional treatments. These results are in line with previously reported concentrations, by Erixon et al [2] and Okabe et al [34]. This observation indicates that the composition being used in this study as well as the analytical procedures is adequate.…”
Section: Resultssupporting
confidence: 93%
“…It appears that using the ohmic heating at 1258C does not form at all or form minor concentrations of the GDPs tested. When these results are compared to a study conducted by Erixon et al [2] it was observed that immediately after sterilization at 1218C for 40 min (F 0 = 40), the concentration of 3-DG was l230 lM.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…16,17,[24][25][26][27][28] Sterilization of glucose-containing PD solutions in buffer at a pH of 5.5, which is typical for conventional standard solutions, unfortunately is far from optimal and leads to a signifi cant amount of GDPs. 29,30 Data suggest that the acidic pH that is a feature of all conventional and some new solutions has toxic effects. Investigating the cytotoxicity of different components of standard PD solutions, Wieslander showed that a pH of 5.5 inhibited cell growth to 100%, while lactate at neutral pH had no signifi cant adverse effect.…”
Section: Safety and Effi Cacymentioning
confidence: 99%